Training for a transformed service: the experience of learners in 2016 - Smyth, Graham (Probation journal, 2018)
This article explores the training and early practice experience of the first cohort of probation learners trained under the auspices of ‘Transforming Rehabilitation’ (TR). It draws on interviews with learners qualifying in 2016 in order to examine the adequacy of their training and their early perceptions of delivering TR as qualified practitioners. While highlighting their training as stressful and noting issues with TR and some implications of the highly risk-focused nature of NPS work in particular, participants were generally positive about their training and early post-qualification experiences. Some inferences are drawn in relation to the future approach to training.